c.1 - "Ranchan, O. P." (Delhi, 2000)
Using a variety of perspectives, the book deals with the subject of happiness in its entirety. An happiness which is, given average good fortune, independent of the external circumstances. Indeed, we discover life to be unfathomable ecstasy if we actualize creative living which comes with the optimal growth of all our human powers-sensory, emotional and intellectual.
Keywords: Happiness